Morphological and Chemical Characteristics of Different Titanium Surfaces Treated by Bicarbonate and Glycine Powder Air Abrasive Systems. Issue 1 (February 2015) - Menini, Maria; Piccardo, Paolo; Baldi, Domenico; Dellepiane, Elena; Pera, Paolo
Abstract : Objectives: This in vitro study investigated possible morphological and chemical changes induced by glycine or sodium bicarbonate powder air polishing on machined and acid-etched titanium surfaces. Materials and Methods: The glycine powder (granulometry <65 μm) and sodium bicarbonate powder (granulometry <150 μm) were applied on 2 machined healing abutments and on 2 acid-etched healing abutments. The samples were characterized by scanning electron microscopy coupled with energy dispersive x-ray spectroscopy. The analyses were performed at different steps: (1) as received, right after opening the abutment packaging; (2) after 20 minutes air exposure; (3) after aging in artificial saliva; (4) after glycine or sodium bicarbonate powder air polishing for 5 seconds; (5) after repetition of steps 3 and 4 with longer time of polishing (20 seconds). Conclusions: Air polishing using glycine and sodium bicarbonate powder seemed to be safe for professional oral hygiene of titanium dental implants, although acid-etched abutments and abutments treated with bicarbonate harbored more salts. This might indicate a greater plaque accumulation in a clinical situation. However, this result has to be investigated in vivo to understand its clinical relevance.